Epigallocatechin Gallate Alleviates Lipopolysaccharide-Induced Intestinal Inflammation in Wenchang Chicken by Inhibiting the TLR4/MyD88/NF-κB Signaling Pathway - Xin Xu; Kunpeng Li; Qian Liu; Haiwen Zhang; Lianbin Li (Veterinary Sciences)
Intestinal inflammation significantly compromises broiler health and adversely affects growth performance. Epigallocatechin gallate (EGCG) was found to maintain the gut health of animals. However, the role and mechanism of EGCG in preventing lipopolysaccharide (LPS)-induced intestinal inflammation in chicks have not yet been fully elucidated. In the 35-day study, 140 one-day-old Wenchang chickens were randomly assigned to four treatments: CON (basal diet), LPS (basal diet + 1 mg/kg body weight (BW) LPS), L-EGCG (basal diet + 40 mg/kg BW EGCG + 1 mg/kg BW LPS), and H-EGCG (basal diet + 60 mg/kg BW EGCG + 1 mg/kg BW LPS). On days 31, 33, and 35 of age, broilers in the LPS, L-EGCG, and H-EGCG treatments received intraperitoneal injections of LPS. The LPS reduced jejunal villus height, villus height/crypt depth ratio, Claudin1 mRNA, catalase (CAT) activity, and interleukin-10 (IL-10) levels compared to CON while elevating diamine oxidase (DAO), interleukin-1β (IL-1β), and tumor necrosis factor α (TNF-α). EGCG improved growth performance in LPS-challenged broilers, elevating jejunal villus height and Claudin1/ZO-1 mRNA with reduced serum DAO. It enhanced antioxidant capacity via increased serum total antioxidant capacity (T-AOC), total superoxide dismutase (T-SOD), CAT, glutathione peroxidase (GSH-Px) activities, and a decreased malondialdehyde (MDA) concentration. Concurrently, EGCG lowered IL-1β/TNF-α and raised IL-10 in serum/jejunum. Crucially, EGCG suppressed jejunal TLR4/MyD88/NF-κB mRNA and protein expression under LPS. These findings demonstrate EGCG’s protective role against LPS-induced intestinal inflammation in Wenchang chickens through TLR4/MyD88/NF-κB pathway inhibition.